Besim Ömer Paşa : (1862-1940) - Ödemiş, Sabahattin (My University, 2013)
Osmanlı Devleti’nde, 19. yüzyılda yenileşme hareketleri önce askerî alanda başlamıştı. Askerî yeniliklerle paralel olarak yeni tıp okulları açılmış, daha sonra bu tıp okulları sivil alana doğru yayılmıştı. Tıbbiyelerin kurulması, nihayetinde İstanbul Tıp Fakültesinin açılması bu yönde adımlardı. Askeri Tıbbiye’de yetişen, ardından Paris’te uzmanlık eğitimi alan Besim Ömer Paşa’nın yaşam öyküsünü, doğumu, eğitimi, çalıştığı kurumlar, muhtelif görevleri, sivil toplum yöneticilikleri ve milletvekillikleri ile birlikte ele alınmış olup Osmanlı Devleti’nde başlayıp ve Türkiye Cumhuriyeti’nde vefat eden bir hayat serüveninden bahsedilmektedir. Besim Ömer Akalın, ardında binlerce sağlıklı insan, 100 e yakın eser, yüzlerce konferans, binlerce yetişmiş öğrenci ve bu ülke insanın sağlığına harcanmış yaklaşık 60 yıllık hizmet bırakmıştır.

In the 19. century the Ottoman Empire reform movements had begun before the military area. In parallel with the military innovations, new medical schools opened, then this is the right medicine schools spread into the civilian sector. The establishment of medical school, and ultimately the opening of the Faculty of Medicine steps in this direction. Growing military medical school, and then specialty training in Paris, Besim Omer Pasha life story, birth, education, work organizations, various tasks have been taken in conjunction with civil society, as parlaımenterian, managements and the Republic of Turkey, who died in the Ottoman Empire and the beginning life adventure belonging mentioned. Besim Ömer AKALIN Behind thousands of healthy people, close to 100 works, conferences, and thousands of students and nearly 60 years of dedicated service to this country has left.
Keywords: Besim Ömer Paşa; Osmanlı İmparatorluğu, 1299-1918; Tarih; Türkiye